Abeta-induced presynaptic release of UBC9 through extracellular vesicles involves SNAP23. (10th August 2022) - Long, Yan; Cheng, Yuanyuan; Yang, Juan; Yang, Tingting; Lai, Yujie
Highlight: Aβ induces the redistribution of UBC9 from presynaptic to postsynaptic terminals. Aβ mediates presynaptic release of UBC9 by extracellular vesicles. SNAP-23 is involved in extracellular vesicles-mediated presynaptic release of UBC9. Phosphorylation of SNAP-23 promoted Aβ-induced presynaptic release of UBC9. The study reveals the mechanism of extracellular vesicles-mediated presynaptic release of UBC9. Abstract: Ubiquitin conjugating enzyme 9 (UBC9), the sole small ubiquitin-like modifier (SUMO) conjugating enzyme, is considered to be a vital regulator of the mechanism of SUMOylation and is likely to participate in the progression of Alzheimer's disease (AD). Our previous studies found that UBC9 is highly mobile in neurons, but the underlying mechanism is still unknown. We designed to investigate the underlying mechanism of the synaptic redistribution of UBC9 in AD. We found that β-amyloid peptide (Aβ) significantly decreased presynaptic UBC9 expression and increased postsynaptic UBC9 expression but did not affect UBC9 expression in synaptosomes. Moreover, there is evidence that extracellular vesicles (EVs) may facilitate synaptic gap transmission. Immunoprecipitation assays showed that flotillin, which is specifically expressed in EVs, co-immunoprecipitated with UBC9 in cell lysates and media and that Aβ treatment enhanced this interaction. Additionally, epidermal growth factor and oleanolic acid have been found to either promote or inhibit the release of EVs, thus blocking the Aβ-induced presynaptic release of UBC9. However, knockdown of synaptosome associated protein 23 (SNAP-23) or inhibition of SNAP23 phosphorylation was found to secure Aβ-induced presynaptic release of UBC9. These results suggest that Aβ induces redistribution of UBC9 from presynaptic to postsynaptic terminals, which may mediate through EVs associated with SNAP23. Our study reveals the cellular mechanisms of EVs as an essential component of the presynaptic release of UBC9.